Dome Form Typology Of Islamic Architecture In Persia - Sahabuddin, Wasilah Sila (Journal of Islamic Architecture, 2017)
Aim of this research is to describe the dome form typology of Islamic Architecture in Persia area. This research applies descriptive qualitative method with physiognomy concept approach as a method in interpreting architecture object. This research methods also identify a particular physical object based on the style of Persian Area (Iran and Middle Asia) which correlated with the origin of dome form. The result explained that the dome typology in Islamic Architecture of Persia style has six types. Most of the types are the development gateway curvature (iwan) as the characteristic feature of Persian architecture.